Effects of light and the regulatory B-subunit composition of protein phosphatase 2A on the susceptibility of Arabidopsis thaliana to aphid (Myzus persicae) infestation - Brwa Rasool; Barbara Karpinska; Grzegorz Konert; Guido Durian; Konstantin Denessiouk; Saijaliisa Kangasjärvi; Christine H. Foyer (Switzerland, 2022)
The interactions between biotic and abiotic stress signaling pathways are complex and poorly understood but protein kinase/phosphatase cascades are potentially important components. Aphid fecundity and susceptibility to Pseudomonas syringae infection were determined in the low light-grown Arabidopsis thaliana wild type and in mutant lines defective in either the protein phosphatase (PP)2A regulatory subunit B'γ (gamma; pp2a-b'γ) or B'ζ (zeta; pp2a-b'ζ1-1 and pp2a-b'ζ 1-2) and in gamma zeta double mutants (pp2a-b'γζ) lacking both subunits. All the mutants except for pp2a-b'ζ 1-1 had significantly lower leaf areas than the wild type. Susceptibility to P. syringae was similar in all genotypes. In contrast, aphid fecundity was significantly decreased in the pp2a-b'γ mutant relative to the wild type but not in the pp2a-b'γζ double mutant. A high light pre-treatment, which led to a significant increase in rosette growth in all mutant lines but not in the wild type, led to a significant decrease in aphid fecundity in all genotypes. The high light pre-treatment abolished the differences in aphid resistance observed in the pp2a-b'γ mutant relative to the wild type. The light and CO2 response curves for photosynthesis were changed in response to the high light pre-treatment, but the high light effects were similar in all genotypes. These data demonstrate that a pre-exposure to high light and the composition of B-subunits on the trimeric PP2A holoenzymes are important in regulating plant resistance to aphids. The functional specificity for the individual regulatory B-subunits may therefore limit aphid colonization, depending on the prevailing abiotic stress environment.